Group-based distributed computing: Programming and distributed platform model. - Farooqui, Kazi. (University of Ottawa (Canada), 2000)
Much research has been done in the past in the area of group communication. However most of this research exists in the low-level support for group communication, such as different types of ordered and reliable multicast protocols, membership management protocols, virtual synchrony, replication techniques, etc. Most of this research provides only low-level pieces of the complete puzzle. The big picture involves a vision of group-based distributed computing . This vision calls for a shift of focus from low-level issues of group communication to the high-level issues of an overall distributed environment capable of supporting group-based distributed computing applications . This thesis is focussed on the dual models of the distributed environment---the distributed programming model and the distributed platform model, required for the support of group-based distributed computing applications. The thesis presents the software architecture of an agent-based and policy-driven group support platform in an implementation independent manner. This is an extensible, configurable and programmable software architecture which permits the separation of group coordination aspects from the application issues. The goal is to enhance the level of middleware support provided by the current generation of distributed platforms such as CORBA. The thesis identifies a set of "middleware-level" group support services (GSSs), such as message distribution service, collation service, synchronisation service, filtering service, etc. commonly required by group-based applications and the corresponding group support agents (GSAs). The thesis presents a framework for the organisation of these group support agents. This framework is called the group support machine (GSM). This thesis is based upon the architectural principles underlying object-based distributed systems architectures such as RM-ODP, ANSA, ROSA, OMA, etc., and is scoped within the ODP computational and engineering models. (Abstract shortened by UMI.)
Keywords: Computer Science.